Thread embedding acupuncture for musculoskeletal pain: a systematic review and meta-analysis protocol. Issue 1 (26th January 2018) - Cho, Yeeun; Lee, Seunghoon; Kim, Jihye; Kang, Jung Won; Lee, Jae-Dong
Abstract : Introduction: Thread embedding acupuncture (TEA) is a special type of acupuncture that inserts certain medical threads (eg, catgut or polydioxanone) into subcutaneous tissue or muscles at specific points. Although TEA has been widely used for the treatment of musculoskeletal pain in Korea, China and Taiwan, evidence regarding its efficacy is lacking. The aim of this protocol is to evaluate the effectiveness and safety of TEA in the treatment of musculoskeletal pain, by conducting a systematic review and meta-analysis. Methods and analysis: The following 16 databases will be searched from their inception to 14 May 2017: MEDLINE, the Cochrane Central Register of Controlled Trials, EMBASE, the Cumulative Index to Nursing and Allied Health Literature, the Allied and Complementary Medicine Database, three Chinese database (China National Knowledge Infrastructure, the Chongqing VIP Chinese Science and Technology Periodical Database and the Wanfang database) and eight Korean databases (Korean Medical Database, Korean Association of Medical Journal Editors, Korean Studies Information Service System, Korean National Assembly Digital Library, National Digital Science Library, Oriental Medicine Advanced Searching Integrated System, 'Database Periodical Information Academic and Korean Traditional Knowledge Portal'). The WHO International Clinical Trials Registry Platform will also be searched to retrieve the recently completed studies. All randomised controlled studies in which TEA was used on specific points for the treatment of musculoskeletal pain will be included and no restrictions on language will be applied. The risk of bias of each study will be evaluated by the Cochrane risk of bias tool. Mean difference or standardised mean difference for continuous data and risk ratio for dichotomous data will be calculated with 95% CIs using a random effects model or a fixed effects model. Additional subgroup and sensitivity analyses will be conducted according to a predefined protocol. Ethics and dissemination: No ethical issues are predicted. The systematic review will be published in a peer-reviewed journal or conference presentation. These findings will summarise the current evidence of TEA for the treatment of musculoskeletal pain and may provide guidance for clinicians and patients to select TEA for musculoskeletal pain. PROSPERO registration number: CRD42015019046.